Epidermal growth factor receptor inhibitory activity of new potential antitumor di(hetero)arylethers and di(hetero)arylamines in the thieno[3,2-b]pyridine series - Calhelha, Ricardo C. (2014)
Thienopyridine skeleton has been reported as having interesting biological activity, namely as antitumorals [1] and antiangiogenics [2]. The Epidermal Growth Factor Receptor (EGFR) exists in the cell surface and is activated by binding its specific ligands. The inhibition of its intracellular tyrosine kinase domain prevents the signaling pathways of cellular proliferation [3]. In our research group we have prepared the di(hetero)arylethers 1a-f and the di(hetero)arylamines 2a-f functionalizing the 7-position of the thieno[3,2-b]pyridine in good to high yields, using copper (C-O) or palladium (C-N) catalyzed couplings, like presented below.The di(hetero)arylethers 1a-f and di(hetero)arylamines 2a-f series were evaluated for EGFR tyrosine kinase inhibition activity. Compounds for series 1 presented practically no or very weak inhibition activity while compounds 2 presented good inhibition activity, with the most potent compounds 2e presenting a IC50 value of 40 nM. These compounds can be view as good starting points for the synthesis of even more potent EGFR inhibitors.